The use of bacterial culture for Leptospirosis di- agnosis in female water buffaloes - Rosaura Pérez-Gil; Oriana Gavidia; Juan Torres (Revista Científica)
The test most used for leptospirosis diagnosis is the Microagglutination Test (MAT). However, the low antibody titers in chronic infections induced by strains adapted to bovines can limit the interpretation of the correct results. The bacteriological culture of Leptospira spp. is the gold standard test because it can demonstrate the agent’s presence. Therefore, this research aimed to reveal the presence of Leptospira spp. in aborted fetuses, genital-urinary secretions of female and male Bubalus bubalis, food raw materials, and rodent feces using bacteriological culture. The analyses were performed on a farm located in the state of Cojedes, Venezuela. This farm has an abortion rate of 17,05% and 2,98% mortality at birth. For this, 18 blood samples (16 females and two males) were extracted by puncture of the jugular vein, and these were allowed to coagulate to obtain the serum and urine samples from 2 female buffaloes, one male buffalo, and semen from 2 other animals, were collected. Additionally, two fetuses of 120 and 75 days of gestation were collected. Also, after the necropsy, fluid samples were obtained from the abdomen, umbilical artery, ocular and thoracic cavities, and amniotic liquid, and two samples of liver, spleen, kidney, lung, heart, and brain were collected. Furthermore, samples of food ration and of the four by-products (corn silage, hay, urea, mineral) that compose it were collected, besides the rodent feces found in the storage where the food was preserved. The standard serological MAT was performed with a panel of strains of 7 Leptospira serovars. The fluids and tissue samples were inoculated in Ellinghausen–McCullough–Johnson–Harris medium (EMJH), a liquid culture medium selective for Leptospira. A portion of the tissue sample was fixed in 10% buffered formalin for histological slices and routine H-E staining. The MAT results indicated titers of 1:50 for the Icterohaem morragiae serovar at 5.5%, Pomona at 5.5%, and Bratislava at 5.5%. The serovars Canicola, Grippotyphosa, Harjo bovis, and Harjo pratjino were negative. There was a growth of Leptospira spp. in fetal fluids from the abdomen, umbilicus, thorax, liver, spleen, lung, kidney, and heart tissues; in the same way, Lepto spira spp. growth was obtained after the culture of urine and semen samples, food, corn silage, hay, urea-mineral and rodent feces. Histopathology analysis showed lesions in the spleen as extra-medullary hematopoiesis and hemorrhage; in the kidney (multifocal hemorrhages, tubular degeneration, and edema) while in the lungs, perivascular hemorrhages and degeneration of the vascular wall were observed. In conclusion, these preliminary results suggest that the MAT cannot diagnose all Leptospirosis cases correctly, especially chronic infections characterized by low antibodies. At the same time, the culture in EMJH seems to solve this weakness, as Leptospira spp. growth was obtained from different biological samples. Additionally, these preliminary findings confirm Leptospira is an agent involved in abortions, as we obtained Leptospira spp. growth from aborted fetus samples. Finally, it is likely that this bacterium growing in the bacteriological cultures belongs to a serovar different from those in the panel of strains used in MAT, so the cultures were preserved for subsequent studies that contemplate molecular identification.